Progressive Systemic Sclerosis with Interstitial Lung Disease Post Radio Ablationin Graves Disease's Patient: A Case Report - Maha Chakri Willheljulya (Indonesian Journal of Rheumatology, 2021)
Systemic sclerosis (SSc) is a connective tissue disease marked by degenerativemicrovascular abnormalities and immune system activation, resulting in skin andinternal organ fibrosis. The link between thyroid problems and systemic sclerosisis unknown. Although several studies have demonstrated that patients withsystemic sclerosis develop Graves' illness as the condition progresses, only a fewhave reported that Graves' patients develop progressive systemic sclerosis. It is anuncommon instance of multiple autoimmune illnesses in which SSc developsgradually after the birth of the first child and the patient had Graves' disease sincethe age of 17 and had thyroid ablation 5 years ago. SSc illness has a characteristicclinical appearance, involving the skin to the rest of the body and internal organs,particularly the lungs.